Students’ Perception of English Online Learning During Covid-19 in North Sumatera - Muhammad Dalimunte; Sholihatul Hamidah Dulay; Siti Handayani (STAI Hubbulwathan Duri, 2023)
With the impact of Covid-19, everything has been changing especially in the education field. The learning-teaching process transforms into an online platform. This is one of the alternative solutions to the COVID-19 pandemic era, But the transition from the offline class to the online class has proved challenging for some students and teachers. The purpose of this study was to analyze why students do not perceive online classrooms as providing the same learning experience as the traditional classroom. The Research questions are about the perceptions and experiences of the Senior High School students in North Sumatra in the online classroom as opposed to the traditional classroom during the Covid-19 pandemic. The Qualitative descriptive approach was used in this research. There were 24 students of senior High School from different schools taken as participants. The Data were collected through questionnaires which were distributed to the students and interviewed. The research findings showed that students prefer classroom learning (offline meetings) to online learning for some reasons. The results of the study will help school administrators focus on making the online class more engaging for students.